2018
DOI: 10.5194/amt-11-5363-2018
|View full text |Cite
|
Sign up to set email alerts
|

The instrument constant of sky radiometers (POM-02) – Part 1: Calibration constant

Abstract: Abstract. Ground-based networks have been developed to determine the spatiotemporal distribution of the optical properties of aerosols using radiometers. In this study, the precision of the calibration constant (V0) for the sky radiometer (POM-02) that is used by SKYNET was investigated. The temperature dependence of the sensor output was also investigated, and the dependence in the 340, 380, and 2200 nm channels was found to be larger than for other channels and varied with the instrument. In the summer, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The merit of the method is that we can narrow the size of the point source below 0.5° and can extend the CSD size beyond ±1° without significant effect of the sky light. Analyzing data from the solar disk scan and lamp scan methods, Uchiyama et al, (2018b) found an underestimation of SVA from the disk scan method of 0.5 % to 1.9 % and proposed a correction method by extending CSD size up to scattering angle of 2.5° assuming an extrapolation function as illustrated in Fig. 7.…”
Section: Sky Radiance Calibration For the Sky Radiometermentioning
confidence: 99%
“…The merit of the method is that we can narrow the size of the point source below 0.5° and can extend the CSD size beyond ±1° without significant effect of the sky light. Analyzing data from the solar disk scan and lamp scan methods, Uchiyama et al, (2018b) found an underestimation of SVA from the disk scan method of 0.5 % to 1.9 % and proposed a correction method by extending CSD size up to scattering angle of 2.5° assuming an extrapolation function as illustrated in Fig. 7.…”
Section: Sky Radiance Calibration For the Sky Radiometermentioning
confidence: 99%
“…Several satellite programs provide aerosol optical depth data on a global scale: for example, the Moderate Resolution Imaging Spectroradiometer (MODIS) (Remer et al, 2005), Multiangle Imaging Spectroradiometer (MISR) (Kahn et al, 2005), Geostationary Operational Environmental Satellite (GOES) Aerosol/Smoke Product (GASP) (Prados et al, 2007), Sea-viewing Wide Field-of-view Sensor (SeaWiFS) (Wang et al, 2000), Advanced Himawari Imager (AHI) (Yoshida et al, 2018;Kikuchi et al, 2018), and Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) (Winker et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This output at the mean earth-sun 307 distance (1 AU) at the reference temperature is called the calibration constant. In 308 this study, the calibration constant was determined by the Langley method 309 (Uchiyama et al 2018). Here, we do not consider the temperature dependence of the 310 sensor output for the POM-02.…”
mentioning
confidence: 99%
“…Here, we do not consider the temperature dependence of the 310 sensor output for the POM-02. Under these observation conditions in Tsukuba, the 311 temperature dependence of the sensor output can be ignored except for the 340, 380, 312 and 2200 nm channels (Uchiyama et al 2018). 313…”
mentioning
confidence: 99%